Students' Activity in Online Learning Application Using LAPS-Heuristic Model in Geometry Material - Anis Farida Jamil; Mayang Dintarini (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
During the Covid-19 pandemic, learning was fully carried out online. However, the implementation of learning is still not optimal, especially in evaluating student activities.Using online learning, lecturers have difficulty observing student activities, and mostly, online learning was done using assignments or even a teacher-centered. This research was expected to accommodate the application of online learning by the student center using the LAPS-Heuristic model. This study aims to describe student activities in the application of online learning using the Logan Avanue Problem Solving (LAPS)-Heuristic model on geometry material. This research uses a descriptive qualitative-quantitative approach. The research steps were carried out, starting from research planning, implementing the LAPS-Heuristic model online, analyzing, and evaluating activities. Student activity data were obtained from observations made by researchers and one observer. Based on the findings in the study, student activities in the application of online learning using the LAPS-Heuristic model on geometry material are described in 7 aspects. The seven aspects are visual, verbal, listening, writing, drawing, calculating / problem solving, and emotional aspects. In learning reflection material online by applying the LAPS Heuristic learning model, the seven aspects of the activity appear very well.